Colonization of a portion of the bovine tongue by unusual filamentous bacteria. - McCowan, R P (1979)
Tongue samples from cattle on varied diets and ranging in age from 2 months to adult were studied by transmission and scanning electron microscopy to observe the in situ distribution and adhesion patterns of two readily identifiable genera of filamentous bacterial. The two, both members of the Simonsiellaceae, adhere to the epithelium by means of fibers which are produced on one side of the bacterial filaments and subsequently display a sidedness in their manner of adhesion to epithelial surfaces. Other bacterial populations found on the tongue were normally members of chains and seldom present as single cells. This suggests that filamentous or chain-forming bacteria may have a selective advantage over single bacteria in their ability to colonize and remain attached to the epithelium of the tongue.